A complete set of pnictocarbynes: [M(CAPh2)(CO)2(Tp*)] (M = Mo, W; A = N, P, As, Sb, Bi; Tp* = hydrotris(dimethylpyrazolyl)-borate). Issue 17 (8th February 2018) - Frogley, Benjamin J.; Hill, Anthony F.
Abstract : The first two complete series of pnictogen functionalised carbyne complexes, [M(CAPh2 )(CO)2 (Tp*)] (M = Mo, W; A = N, P, As, Sb, Bi; Tp* = hydrotris(3, 5-dimethylpyrazol-1-yl)borate), have been prepared. Abstract : The first two complete series of pnictogen functionalised carbyne complexes, [M(CAPh2 )(CO)2 (Tp*)] (M = Mo, W; A = N, P, As, Sb, Bi; Tp* = hydrotris(3, 5-dimethylpyrazol-1-yl)borate), have been prepared. The heavier analogues (A ≠ N) result from successive treatment of [M(CBr)(CO)2 (Tp*)] with n BuLi and ClAPPh2 (A = P, Sb, Bi) or BrAsPh2 and include the first examples of arsino, stibino or bismuthino carbyne complexes.